Obesity indices and their sociodemographic, lifestyle, and social isolation correlates in a large Spanish working population - Riutord-Sbert, Pere; Tárraga López, Pedro Juan; López-González, Ángel Arturo; Coll Campayo, Irene; Busquets-Cortés, Carla; Ramírez Manent, José Ignacio (Frontiers in Endocrinology, 2025)
BackgroundObesity is a multifactorial condition shaped by biological, behavioral, socioeconomic, and psychosocial determinants. While lifestyle correlates are well documented, the impact of social isolation on obesity in occupational settings remains insufficiently explored. This study examined associations between sociodemographic variables, health behaviors, and social isolation with multiple obesity indices in a large cohort of Spanish workers.MethodsWe analyzed 117298 employees across Spain (2021–2024). Obesity was defined using body mass index (BMI), waist-to-height ratio (WtHR), Clínica Universidad de Navarra–Body Adiposity Estimator (CUN-BAE), and Metabolic Score for Visceral Fat (METS-VF). Sociodemographic data, lifestyle habits, and social isolation (ENRICHD Social Support Instrument, ESSI) were obtained through standardized protocols. Multivariable logistic regression estimated adjusted odds ratios (OR) and 95% confidence intervals (CI).ResultsObesity prevalence ranged from 20.4% (BMI) to 39.6% (METS-VF). Male sex (OR up to 2.11, 95% CI 2.05–2.18), older age (OR 2.83, 95% CI 2.71–2.96 for ≥55 years vs. <35), and lower social class (OR 1.62, 95% CI 1.54–1.71) were consistently associated with obesity across all indices. Poor adherence to the Mediterranean diet and physical inactivity increased the likelihood of obesity (OR 1.35 and 1.41, respectively). Social isolation independently predicted higher obesity risk (OR 1.27, 95% CI 1.21–1.33), even after adjusting for sociodemographic and lifestyle factors. Associations remained robust in sensitivity analyses.ConclusionsObesity in Spanish workers is strongly associated with sociodemographic disadvantage, unhealthy lifestyles, and psychosocial vulnerability. Social isolation emerged as a novel determinant, reinforcing the need for multidimensional public health strategies that integrate lifestyle promotion, reduction of socioeconomic inequalities, and enhancement of social connectedness.